7 beta-hydroperoxycholest-5-en-3 beta-ol, a component of human atherosclerotic lesions, is the primary cytotoxin of oxidized human low density lipoprotein. - G M Chisolm; Guoping Ma; K. C. Irwin; LJ Martin; Karl Gunderson; L. F. Linberg; Diane W. Morel; Paul E. DiCorleto (1994)
Modification of low density lipoprotein (LDL) by free radical oxidation renders this molecular complex cytotoxic. Oxidized lipoproteins exist in vivo in atherosclerotic lesions and in the plasma of diabetic animals, suggesting that lipoprotein-induced tissue damage may occur in certain diseases. We undertook purification and identification of the major cytotoxin in oxidized LDL. The lipid extract from oxidized LDL was subjected to multiple HPLC separations, and the fractions were assayed for cytotoxicity. Mass spectrometry and nuclear magnetic resonance identified the purified toxin as 7 beta-hydroperoxycholest-5-en-3 beta-ol (7 beta-OOH-Chol). This molecule accounted for approximately 90% of the cytotoxicity of the lipids of oxidized LDL. We also found 7 beta-OOH-Chol in human atherosclerotic lesions from endarterectomy specimens obtained immediately after excision. These results are consistent with the hypothesis that the oxidized LDL present in lesions has the capacity to induce cell and tissue injury, leading to progression of the disease and the generation of the necrotic core of the lesion.